Comparing primate crania: The importance of fossils. Issue 2 (12th July 2016) - Fleagle, John G.; Gilbert, Christopher C.; Baden, Andrea L.
Abstract: Objectives: Extant primate crania represent a small subset of primate crania that have existed. The main objective here is to examine how the inclusion of fossil crania changes our understanding of primate cranial diversity relative to analyses of extant primates. We hypothesize that fossil taxa will change the major axes of cranial shape, occupy new areas of morphospace, change the relative diversity of major primate clades, and fill in notable gaps separating major primate taxa/clades. Materials and Methods: Eighteen 3D landmarks were collected on 157 extant and fossil crania representing 90 genera. Data were subjected to a Generalized Procrustes Analysis then principal components analysis. Relative diversity between clades was assessed using an F ‐statistic. Results: Fossil taxa do not significantly alter major axes of cranial shape, but they do occupy unique areas of morphospace, change the relative diversity between clades, and fill in notable gaps in primate cranial evolution. Strepsirrhines remain significantly less diverse than anthropoids. Fossil hominins fill the gap in cranial morphospace between extant great apes and modern humans. Discussion: The morphospace outlined by living primates largely includes that occupied by fossil taxa, suggesting that the cranial diversity of living primates generally encompasses the total diversity that has evolved in this Order. The evolution of the anthropoid cranium was a significant event allowing anthropoids to achieve significantly greater cranial diversity compared to strepsirrhines. Fossil taxa fill in notable gaps within and between clades, highlighting their transitional nature and eliminating the appearance of large morphological distances between extant taxa, particularly in the case of extant hominids.